Balanced scorecard as support to management decisions: case study in a small property of milk production - Cardoso, Antônio Augusto Brion; Lopes, Marcos Aurélio; Carvalho, Francisval de Melo; Ferrazza, Rodrigo Andrade; Lima, André Luís Ribeiro; Cardoso, Milton Ghedini (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">Aimed to apply the Balanced Scorecard (BSC) in a dairy farm with small-scale production, located in the south of Minas Gerais State, Brazil. The survey was conducted from January to December 2013 and the gathering of information was carried out through semi-structured interviews on the spot. As data collection instruments were used personal interviews, document analysis and direct and participant observation. The farm object of study had 216 ha, 80% of this, leased. The activities were dairy farming, corresponding to 80% of revenues, and the cultivation of coffee. The breeding farm was 22 predominantly Holstein cows (¾ H) that are loose in the pasture. The daily production was 350 liters average of 15.9 liters of milk per cow in milk, in two daily milkings. The main strength was the low cost of hand labor; while the weaknesses identified were the infrastructure, the lack of management control and planning. The mission created takes into account the increased efficiency in milk production and increase the quality of this product without increasing the herd. At the end, a strategic map, where it was revealed that the objectives growth and efficiency will be achieved taking into account the increase in revenue was proposed. It was found at the end of the study, that the principles of BSC can be applied to a farm producing small milk with some caveats.